'Our Soviet Americanism': Jolly Fellows, Music, and Early Soviet Cultural Ideology. Issue 2 (22nd July 2016) - KUPFER, PETER
Abstract: The musical comedy film was perhaps a surprising genre to appear and flourish in the Soviet Union during the 1930s, a decade traditionally associated with the grimmer realities of Stalin's ruthless consolidation of power, show trials, and purges. Despite (and in many ways because of) this, the musical comedy became quite popular, with audiences and officials alike. Its creation did not, however, proceed without controversy or difficulty. In this article, I examine how director Grigory Aleksandrov and composer Isaak Dunayevsky drew on well-known and well-liked American musical and cinematic models to construct the first Soviet musical comedy film, Jolly Fellows (1934), and the role of music in the controversy that the film sparked. I argue that in choosing musical content appropriate for contemporary Soviet viewers and transmitting it by using American-inspired formal structures that rely on music, Aleksandrov and Dunayevsky created a powerful hybrid that spoke convincingly to audiences and critics, who ultimately used the film and its music as a means for debating issues of cultural significance.